Spatial Analysis of the Semeru Eruption Disaster Area - Utami, W.; Sugiyanto, C.; Rahardjo, N.; Juliyani, A.; Richasari, D.S.; Nurhadi, N. (Association for Geoinformation Technology, 2023)
Semeru, the most active volcano in Indonesia, erupted again in December 2021. This study aimed to map the impact of damages due to the eruption and map the incompatibility of land use with the Spatial Planning. The study was carried out through multitemporal spatial analysis to map the impact of the eruption damages, while the analysis of suitability and land use direction was carried out by overlaying land use maps with Spatial Planning maps. Sentinel-1B image data were analyzed using a maximum likelihood approach to obtain land use classification before and after the eruption. The results of the study showed that the eruption had an impact on the destruction of 1001.2 Ha of High-Density Forest, 624.9 Ha of Medium-Density Forest, 450.8 Ha of Rice Fields, 436.7 Ha of Agricultural Fields, 91 Ha of Settlements, and 3.1 Ha of Water bodies in Lumajang Regency. The results of the analysis show that in the affected area, there is a spatial plan direction of a residential area of 109.7 Ha. In addition to that, the high impact of the disaster is also due to the incompatibility of land use in the conservation area as a residential area of 515.4 Ha. © Geoinformatics International.